Forcings and Evolution of the 2017 Coastal El Niño Off Northern Peru and Ecuador - Echevin, Vincent; Colas, Francois; Espinoza-Morriberon, Dante; Vasquez, Luis; Anculle, Tony; Gutierrez, Dimitri (Frontiers in Marine Science, 2018)
El Niño events, in particular the Eastern Pacific type, have a tremendous impact on the marine ecosystem and climate conditions in the Eastern South Pacific. During such events, the accumulation of anomalously warm waters along the coast favors intense rainfall. The upwelling of nutrient-replete waters is stopped and the marine ecosystem is strongly impacted. These events are generally associated with positive surface temperature anomalies in the Central and Eastern equatorial Pacific. During austral summer 2017, a strong surface temperature anomaly reaching ~3-4°C off Northern Peru and Ecuador led to intense coastal precipitations. However, neutral temperature anomalies were recorded in the equatorial Pacific. Using in situ measurements, satellite observations, and simulations from a eddy-resolving regional ocean circulation model, we investigate the physical processes triggering this peculiar 'coastal El Niño'. Its impact on the regional ocean circulation and heat budget off northern Peru and Ecuador is assessed. Using model sensitivity experiments, we investigate the respective roles of the equatorial Kelvin waves and local wind anomalies in driving the anomalously high nearshore SST. The atmospheric teleconnections which triggered the event are investigated using reanalysis data.